2020
DOI: 10.3390/jcm9103118
|View full text |Cite
|
Sign up to set email alerts
|

Menstrual Phase Affects Coagulation and Hematological Parameters during Central Hypovolemia

Abstract: Background: It has been reported that women have a higher number of heart attacks in the “follicular phase” of the menstrual cycle. We, therefore, tested the hypothesis that women in the follicular phase exhibit higher coagulability. As lower body negative pressure (LBNP) has been used previously to assess coagulation changes in whole blood (WB) samples in men and women, effects of menstrual phase on coagulation was assessed during LBNP. Methods: Seven women, all healthy young participants, with no histories o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 32 publications
(49 reference statements)
0
2
1
Order By: Relevance
“…These ndings also contradicted a study conducted in the United States of America (15), which showed that PT levels were comparable between menorrhagic and non-menorrhagic women. The prolonged PT and INR and their association with menorrhagia in the current study could be attributed to the fact that women in the mid-luteal phase are more hypercoagulable than women in the early follicular phase (33). Most of those previous investigations associated prothrombin time with adenomyosis (34) but not directly with menorrhagia.…”
Section: Discussioncontrasting
confidence: 40%
“…These ndings also contradicted a study conducted in the United States of America (15), which showed that PT levels were comparable between menorrhagic and non-menorrhagic women. The prolonged PT and INR and their association with menorrhagia in the current study could be attributed to the fact that women in the mid-luteal phase are more hypercoagulable than women in the early follicular phase (33). Most of those previous investigations associated prothrombin time with adenomyosis (34) but not directly with menorrhagia.…”
Section: Discussioncontrasting
confidence: 40%
“…An important limitation of this study is that the data shown here are pooled data from males and females and also do not take into account menstrual cycle phases or whether the females were taking oral contraceptives (OCs). While this could be a limitation, as the sex of the participants (Cvirn et al 2019) [3] and the menstrual phases (Goswami et al 2020) [51] are known to affect coagulation, we did not include these aspects in our data analysis, as assessment of differences across the sexes or phases of the menstrual cycle were not the aims of this study. Future studies should examine effects of seasons on coagulation parameters across the sexes of the participants and phases of the menstrual cycle.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, LBNP alone or in combination with head up tilt (HUT) has been used to assess systemic responses as subjects reach the end of their cardiovascular stability and develop a presyncopal state (9). Coagulatory activities have also been studied during LBNP (6,10,11) and at presyncope (12). Studying the impact of LBNP activity in the laboratory setting can also reinforce the need to identify possible confounding variables that can potentially affect cardiovascular and hormonal responses associated with acute Correspondence: N. Goswami (e-mail: nandu.goswami@medunigraz.at).…”
Section: Introductionmentioning
confidence: 99%